2017
DOI: 10.15446/revfacmed.v65n4.59416
|View full text |Cite
|
Sign up to set email alerts
|

Enseñanza de idiomas en escuelas de medicina humana de Perú

Abstract: INVESTIGACIÓN ORIGINAL | Resumen |Introducción. Las escuelas de medicina en Latinoamérica deberían asegurar que sus egresados conozcan ciertos idiomas además del español. Sin embargo, poco se ha descrito sobre el tema en Perú.Objetivo. Describir las características de la enseñanza de otros idiomas en escuelas de medicina humana de Perú. Materiales y métodos.Estudio transversal analítico realizado durante agosto de 2015 en escuelas de medicina humana de Perú. Se contactaron al menos dos estudiantes de cada escu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…Currently, around 80% of peer-reviewed scientific literature published worldwide is in the English language [ 31 ], meaning it is essential to have a high level of proficiency in English if you wish to keep up-to-date with advances in the field of medicine easily. Although many medical schools have begun offering English as a mandatory part of their academic programs [ 32 ], the level of language learning within these academic programs at Latin American universities is often limited to basic proficiency [ 33 ]. It has previously been reported that university students with intermediate to advanced levels of English proficiency more frequently consult scientific journals than those with basic proficiency [ 33 , 34 ], which our study's findings also demonstrate and verify.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, around 80% of peer-reviewed scientific literature published worldwide is in the English language [ 31 ], meaning it is essential to have a high level of proficiency in English if you wish to keep up-to-date with advances in the field of medicine easily. Although many medical schools have begun offering English as a mandatory part of their academic programs [ 32 ], the level of language learning within these academic programs at Latin American universities is often limited to basic proficiency [ 33 ]. It has previously been reported that university students with intermediate to advanced levels of English proficiency more frequently consult scientific journals than those with basic proficiency [ 33 , 34 ], which our study's findings also demonstrate and verify.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because many private universities can better offer their students opportunities for learning the English language to levels of proficiency higher than those attained in the mandatory academic programs of public universities, largely due to the financial restrictions faced by the latter. In addition, given that English is generally an elective and not a mandatory subject in private universities [ 32 ], these students often display greater personal interest and aspirations in the subject than automatically enrolled students, alongside the privileged possibility of more access to international literature at private universities.…”
Section: Discussionmentioning
confidence: 99%
“…El manejo de las TIC podría utilizarse, según relatan experiencias docentes, en el aprendizaje de idiomas como nuevos modelos de formación en ciencias de la salud, en particular el idioma inglés (17). En un estudio que incluyó a 37 facultades de Medicina de Perú, el idioma inglés y el idioma quechua eran los principales idiomas incluidos el currículo de medicina de las distintas universidades, todas (100 %) teniendo algún requisito obligatorio para titulación relacionado con el idioma inglés (19). Comparando con nuestro estudio, el idioma guaraní en nivel básico (35,5 %) es manejado por la mayoría de los estudiantes de ciencias de la salud, teniendo en cuenta que nuestra población es bilingüe y resulta interesante su utilización en TIC en los motores búsquedas de información (ejemplo: Google) como idioma de consulta.…”
Section: Discusionunclassified
“…En la base de datos oficial de pueblos indígenas u originarios del Ministerio de Cultura se refiere que a principios del siglo XX el 60% de la población peruana hablaba quechua y a principios del siglo XXI solo el 15% era quechua hablante, siempre coexistiendo con el castellano o español 5 . Estudios recientes reportaron que el idioma quechua se enseña en pocas escuelas de medicina: 3 de 25 escuelas en una investigación 6 , y 6 de 36 en otra 7 . Sólo en 4 escuelas era requisito obligatorio para titularse de médico cirujano.…”
Section: Nivel De Conocimiento Del Idioma Quechua Lengua Indígena VIunclassified